PENGARUH PENAMBAHAN INHIBITOR ORGANIK EKSTRAK ECENG GONDOK TERHADAP LAJU KOROSI - Nani Mulyaningsih; Catur Pramono; Ryan Try Prasetyo (Journal of Mechanical Engineering, 2018)
One of the extracts of natural ingredients can be used as corrosion inhibitors is tannin and lignin in eichornia crassipes plants. The used extract eichornia crassipes as a corrosion inhibitor is very useful for the industrial. The aim of the study was to analyze the effect of inhibitors of eichornia crassipes on the corrosion rate of SIICHASE bolts. This research method by providing inhibitor solutions made from eichornia crassipes to SIICHASE bolt material by inhibitor concentrations of 0%, 9%, 12% and 15%, then tested for corrosion resistance in the seawater. The results showed that the addition of a 12% inhibitor concentration of eichornia crassipes produced the lowest corrosion rate of 10.852 mpy.